Carlos Calderón Chico and his cultural project in Ecuador and America - Handelsman, Michael (Revista Universidad de Guayaquil, 1988)
One of the most fascinating aspects of Latin America is its magical-realistic and fantastic character that surprises and disturbs at every moment. In many ways, America's great vitality and hope lies in its ability to challenge the canons of European logos. Although there is a tendency to relegate "the wonderful real" in Latin America to the exotic, understanding it only as a barbaric phenomenon that attracts the attention of civilized tourists, it goes without saying that it is about something much deeper. Apart from the literary world